The relationship between burnout and work engagement among English teachers of primary schools in Klang, Selangor / Mohd Fitri Abdul Murad - Abdul Murad, Mohd Fitri (2015)
The purpose of this study was to investigate the potential levels and relationship between bumout and work engagement among primary school English teachers in Klang. This study also intended to find out the factors that influence work engagement among English teachers and the elements of these factors. A mixed-methods research approach employing quantitative and qualitative methods of data collection was used; both these methods are widely used in researches relating to bumout and work engagement. In the quantitative section, 120 respondents completed a questionnaire pack comprising the Maslach Bumout Inventory-Educators Survey (MBI-ES) and the Utrecht Work Engagement Scale (UWES-9). Meanwhile for qualitative section, 12 respondents were involved in the themed interview. The Maslach Bumout Inventory and Utrecht Work Engagement Scale were used to assess bumout and work engagement, and its relation respectively. Pearson's Correlation showed no significant relation between three dimensions of bumout and the work engagement. Specifically, English teachers reported higher levels of burnout and high level in work engagement suggesting that the teachers are still committed to their job. Moreover, qualitative findings revealed how bumout influences their engagement and the factor related to their engagement. It is concluded that special attention should be paid to the bumout suffered by the English teachers and how to sustain their work engagement in educational context.